2021
DOI: 10.1186/s12302-021-00453-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to high-concentration silver nanoparticles induced toxicity, fatality, bioaccumulation, and histological alteration in fish (Cyprinus carpio)

Abstract: Background Currently, nanotechnology and nanoparticles have quickly emerged and have gained the attention of scientists due to their massive applications in environmental sectors. However, these environmental applications of silver nanoparticles potentially cause serious effects on terrestrial and aquatic organisms. In the current study, freshwater fish C. carpio were exposed to blood-mediated silver nanoparticles for toxicity, mortality, bioaccumulation, and histological alterations. Silver na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 40 publications
4
34
1
Order By: Relevance
“…Therefore, the accumulation was primarily taking place in the intestines Figure 3 after the liver. Our results are supported by (Kakakhel, Wu, Feng, et al, 2021; Kakakhel, Wu, Sajjad, et al, 2021). Their results revealed that the intestine was the second most accumulated organ regarding AgNPs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, the accumulation was primarily taking place in the intestines Figure 3 after the liver. Our results are supported by (Kakakhel, Wu, Feng, et al, 2021; Kakakhel, Wu, Sajjad, et al, 2021). Their results revealed that the intestine was the second most accumulated organ regarding AgNPs.…”
Section: Discussionsupporting
confidence: 90%
“…Intestines of any animal consist of small finger‐like projection called villi and villi increase surface area for the absorption of any materials. Hence, the intestine absorbed more AgNPs after the liver (Kakakhel, Wu, Feng, et al, 2021; Kakakhel, Wu, Sajjad, et al, 2021). In the current study, the gill was the third most bioaccumulated organ after the liver and intestine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, some scientists are now assessing biological nanotechnology in applied science (Gatenby & Townley, 2003). The applications of biological nanotechnology has received a great attention in fishries, animal husbandry, and conservation as an alternative source for antibiotics and chemical biocide (Kakakhel et al, 2021) because of certain reasons: that is, ecofriendly and low cost with less time consuming (Barberia-Roque, Gámez-Espinosa, Viera, & Bellotti, 2019). The silver nanoparticles (AgNPs) are known to be a broad-spectrum and used mainly in conservation science against different bacterial species (Li et al, 2017).…”
mentioning
confidence: 99%